A general framework for solving Riemann-Hilbert problems numerically - Olver, S (Unspecified, 2010)
A new, numerical framework for the approximation of solutions to matrix-valued Riemann-Hilbert problems is developed, based on a recent method for the homogeneous Painlev\'e II Riemann- Hilbert problem. We demonstrate its effectiveness by computing solutions to other Painlev\'e transcendents. An implementation in MATHEMATICA is made available online.